Safety of immunotherapy in patients with rhinitis, asthma or atopic dermatitis using an ultra-rush buildup. A retrospective study (2014)
ABSTRACT: Background Allergen-specific immunotherapy is a proven, highly effective treatment for IgE–mediated diseases. However, ultra-rush immunotherapy is prescribed infrequently because of the perception that accelerated immunotherapy buildup leads to a higher rate of systemic reactions. Objective To evaluate the frequency of adverse reactions in patients with IgE–mediated diseases receiving house dust mite (HDM) ultra-rush immunotherapy. Methods A retrospective, observational study was conducted for patients with IgE–mediated diseases receiving allergen-specific immunotherapy. Subcutaneous immunotherapy with depigmented polymerized mites extract was administered in two refracted doses of 0.2 and 0.3ml at first injection, and in single 0.5ml doses in subsequent monthly injections. A 30min observation time was required after each injection. Systemic reactions were graded using the World Allergy Organisation grading system. Results 575 patients were included. The age range was 1–83 years. Most patients had respiratory diseases (544) and 101 patients had atopic dermatitis. A total of 27 patients (4.6%) experienced 139 reactions (reactions/injections: 1.9%); 22 patients (3.8%) experienced 134 local reactions (local reactions/injections: 1.8%). Eight patients (1.3%) experienced eight systemic reactions (systemic reactions/injections: 0.1%). Five systemic reactions were grade 2 and three grade 1. Two systemic reactions were reported during buildup. There were no fatalities. Conclusion Taking into account the possible bias for the retrospective design of this study we observed that immunotherapy for patients with IgE–mediated diseases using a depigmented polymerized mites extract, with an ultra-rush buildup, has similar frequency of systemic reactions than that seen in slower buildup immunotherapy in other studies. Accelerated buildup could improve patients’ adherence and reduce dropout rates.